Magnetic anisotropy in rhyolitic ignimbrite, Snake River Plain: Implications for using remanent magnetism of volcanic rocks for correlation, paleomagnetic studies, and geological reconstructions. Issue 6 (16th June 2015) - Finn, David R.; Coe, Robert S.; Kelly, Henry; Branney, Michael; Knott, Thomas; Reichow, Marc
Abstract: Individual ignimbrite cooling units in southern Idaho display significant variation of magnetic remanence directions and other magnetic properties. This complicates paleomagnetic correlation. The ignimbrites are intensely welded and exhibit mylonite‐like flow banding produced by rheomorphic ductile shear during emplacement, prior to cooling below magnetic blocking temperatures. Glassy vitrophyric lithologies commonly have discrepantly shallow remanence directions rotated closer to the orientation of the subhorizontal shear fabric when compared to the microcrystalline center of the same cooling unit. To investigate this problem, we conducted a detailed paleomagnetic and rock magnetic study of a vertical profile through a single ignimbrite cooling unit and its underlying baked soil. The results demonstrate that large anisotropy of thermal remanent magnetization correlates with large (up to 38°) deflections of the stable remanence direction. Anisotropy of magnetic susceptibility revealed no strong anisotropy. A strong lineation and deflection of the remanence declination suggest that rheomorphic shear above magnetic blocking temperatures is the dominant mechanism controlling the formation of the magnetic fabric, with compaction contributing to a lesser extent. Nucleation and growth of anisotropic fine‐grained magnetite in volcanic glass at high temperatures after, and perhaps also during, emplacement is indicated by systematic variation of magnetic properties from the quickly chilled ignimbrite base to the interior. These properties include remanence directions, anisotropy, coercivity, susceptibility, strength of natural remanent magnetization, and dominant unblocking temperature. The microcrystalline ignimbrite center has a magnetic direction that is the same as the underlying baked soil and, therefore, is a more reliable recorder of the paleofield direction than the glassy margins of highly welded ignimbrites. Key Points: Paleomagnetic directions of different ignimbrite sublithologies are compared Crystalline samples record the paleofield direction better than glassy samples Strong magnetic anisotropy affects remanence directions of glassy samples